The collections of Alexandr Sergeyevich Lisetskiy in the ornithological collection of the Museum of Nature of V.N.Karazin Kharkiv National University - Devyatko, T. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
A significant part of the ornithological collection of the Museum of Nature of V.N.Karazin Kharkiv National University is made up of the collections of Alexandr Sergeyevich Lisetskiy: 1292 specimens (of which 1276 skins and 16 stuffed animals), which is almost 7% of the total number of the museum’s ornithological collection (almost 19 thousand items). By species composition Lisetskiy’s collections are represented by 215 species of birds (of which 85 species of non-passerine birds and 130 species of passerine birds). By geographical diversity, the collections of Alexandr Sergeyevich are representing Ukraine (Zaporozhe, Lugansk, Kharkov, Kherson regions and collections from the Autonomous Republic of Crimea), Russia (Volgograd, Murmansk, Sakhalin regions; Kamchatka, Krasnodar Territory, Republic of Dagestan), Turkmenistan (Akhal velayat), Georgia (Tbilisi, Imereti, Autonomous Republic of Adjara) and Armenia. The collections of Alexander Sergeevich Lisetskii significantly enriched the museum’s ornithological collection, replenished it with specimens of rare species represented in the collection as single specimens: the yellow browed warbler Phylloscopus inornatus (Blyth, 1842), a new species in Crimea’s fauna and the only confirmed registration of this species in the area; the Pechora pipit, Anthus gustavi Swinhoe, 1863; the russet sparrow Passer rutilans (Temminck, 1835), the only specimen in the museum’s collection, the narcissus flycatcher Ficedula narcissina (Temminck, 1835) of which only 2 specimen are in the collection and one of them was collected by Alexandr Sergeyevich; as well as the olive-backed pipit Anthus hodgsoni (Richmond, 1907), the Radde’s warbler Phylloscopus schwarzi (Radde, 1863), the eastern rock-nuthatch Sitta tephronota Sharpe, 1872, the grey-necked bunting Emberiza buchanani Blyth, 1844 and others. The collections of Alexandr Sergeyevich presented by skins are stored in the scientific collection of the museum in the stock room in special boxes. Stuffed specimens are on display and are in cabinets or display cases. Each specimen has an inventory number, a detailed label indicating the sex, place and date of extraction, who determines the species, who made the skins or stuffed specimens. Each specimen is listed in the catalog and database of the museum’s ornithological collection.